Motivation Factors Affecting Work Behaviors of the Fish Inspection Officer: Impacts of Motivation Factors on Work Behaviors of Fish Inspection Officers (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purpose of this research was to study the motivating factors affecting the behavior of officers of trade and aquaculture officers.Study employee behavior of trade officials and marine production control and study the relationship between motivation factors and employee behavior.The Department of Aquaculture Control and Production Control The variables used in the research are personal factors of respondents, motivation factors, and work behaviors. By sample group The staff of the Animal Trafficking Control Division and the production factor of 105 people use the questionnaire as a research tool. Data analysis using descriptive statistics Correlation statistics and multiple regression analysis Research results show that most of them are female, age 25-35 years old, studying at the undergraduate level. Working period of 2-5 yearsIs a government official The position of the fishery and operational officer in the border agency Motivation factor in work Found that the overall average was at a high level And work behavior The overall average is at the highest level.The hypothesis testing found that personal factors in terms of gender, age, education level Work period Different types of personnel, positions and work units Affecting work behavior not different And motivation factors Success Respect for Responsibility And progress in the position Influencing work behavior with statistical significance at the confidence level 95